A systematic procedure for the identification of dynamic parameters of robot manipulators - Antonelli, G.; Caccavale, F.; Chiacchio, P. (Robotica, 1999)
In this paper a complete and systematic procedure for the identification of the dynamic parameters of rigid robot manipulators is presented. Starting from the basic results on the subject present in the literature and on a new technique to find exciting trajectories for the estimation, the procedure is developed. A set of algorithms is provided for the implementation of the various steps of the procedure for a generic open-chain structure. The algorithms have been coded in the popular Matlab/Maple environment and the procedure has been tested in a practical case study to identify the dynamic parameters of a six-degree-of-freedom conventional industrial robot.